Photosynthetic characterization of flavodoxin-expressing tobacco plants reveals a high light acclimation-like phenotype - Gomez, Rodrigo Lionel (2020)
Flavodoxins are electron carrier flavoproteins present in bacteria and photosynthetic microorganisms which duplicate the functional properties of iron-sulphur containing ferredoxins and replace them under adverse environmental situations that lead to ferredoxin decline. When expressed in plant chloroplasts, flavodoxin complemented ferredoxin deficiency and improved tolerance to multiple sources of biotic, abiotic and xenobiotic stress. Analysis of flavodoxin-expressing plants grown under normal conditions, in which the two carriers are present, revealed phenotypic effects unrelated to ferredoxin replacement. Flavodoxin thus provided a tool to alter the chloroplast redox poise in a customized way and to investigate its consequences on plant physiology and development. We describe herein the effects exerted by the flavoprotein on the function of the photosynthetic machinery. Pigment analysis revealed significant increases in chlorophyll a, carotenoids and chlorophyll a/b ratio in flavodoxin-expressing tobacco lines. Results suggest smaller antenna size in these plants, supported by lower relative contents of light-harvesting complex proteins. Chlorophyll a fluorescence and P700 spectroscopy measurements indicated that transgenic plants displayed higher quantum yields for both photosystems, a more oxidized plastoquinone pool under steady-state conditions and faster plastoquinone dark oxidation after a pulse of saturating light. Many of these effects resemble the phenotypes exhibited by leaves adapted to high irradiation, a most common environmental hardship faced by plants growing in the field. The results suggest that flavodoxin-expressing plants would be better prepared to cope with this adverse situation, and concur with earlier observations reporting that hundreds of stress-responsive genes were induced in the absence of stress in these lines.